Juventude pobre: arte, psicologia e política - Mônaco, Clarissa Martins [UNESP]; Chagas, Vitor Bonjorno [UNESP]; Nascimento, Roberto Duarte [UNESP]; Bigeli, Alan Ricardo Floriano [UNESP]; Cruz, Murilo Galvão Amâncio [UNESP]; Silva, Samuel Iauany Martins [UNESP]; Silva, Marcelo Lima da [UNESP]; Cruz, Soraia Georgina Ferreira de Paiva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This extension work introduces its main axis that is to intervene with young people considered personal and social risk. We use a perspective that comprises art, psychology and politics. The theoretical basis is based on authors like Foucault, Deleuze, Guattari and others whose method is the cartography. We use the device of "workshops" to forge production of thought and historical appropriation of events through different ways of empowering the subjects with the art, virtualizing other condition modes of existence. Psychology will be an important benchmark as stated in a nonstandardization of poor young people, but rather act empowering them of historical knowledge of how the youth was forged as virtually dangerous.

Este trabalho de extensão tem como eixo principal intervir no processo educacional dos jovens considerados em situação de risco pessoal e social, numa perspectiva que compõe arte, psicologia e política. A base teórica é constituída por autores como Foucault, Deleuze, Guatarri e outros, cujo método é a cartografia. Usamos o dispositivo das “oficinas” para forjarmos a produção de pensamento e a apropriação histórica dos acontecimentos, por meio de diferentes maneiras de potencialização dos sujeitos com a arte, virtualizando outros modos de condição da existência. A psicologia será um importante referencial, na medida que afirma uma não normatização dos jovens pobres, mas sim atuará empoderando-os do conhecimento histórico de como a juventude foi forjada como virtualmente perigosa.
Keywords: Youth; Art; Politics; Juventude; Arte; Política